2020
DOI: 10.33902/jpr.2020063461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of 360 videos when teaching primary school subjects related to environmental education

Abstract: The study presents the results of a project in which 360 o videos were used for informing students about subjects related to environmental education. The target group was forty-four, nine-to ten-year-old students, who used three teaching tools, namely printed material, web pages, and 360o videos. The project lasted for twelve two-teaching-hour sessions (four for each tool), and data were collected by means of evaluation sheets and a questionnaire for recording their views and attitudes. It was found that the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
(104 reference statements)
1
13
0
Order By: Relevance
“…However, in IVR simulations, students do not directly interact with instructors, making it challenging to apply this concept in IVR programmes. There are alternative frameworks that can be used, including the Technology Acceptance Model (TAM) used to design digital information systems and to study the acceptability of technology [12]. A review of TAM involving over 400 articles published between 1999-2017 revealed that the model was widely used in fields related to education [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in IVR simulations, students do not directly interact with instructors, making it challenging to apply this concept in IVR programmes. There are alternative frameworks that can be used, including the Technology Acceptance Model (TAM) used to design digital information systems and to study the acceptability of technology [12]. A review of TAM involving over 400 articles published between 1999-2017 revealed that the model was widely used in fields related to education [70].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the numerous advantages of videos, such as improved understanding and enhanced collaboration [11], they lack certain features that can enhance effectiveness and interest. For example, videos are only shown from one angle, and viewers are usually passive observers, whereas 360-degree videos can be shown from various angles and perspectives [12] and can be viewed on various devices such as smartphones, tablets, and computers (in nonimmersive formats), or as part of an IVR experience via an HMD. HMD IVR packages are becoming increasingly popular in educational applications, as they enable curricula and content to be developed and edited for specific educational purposes [13].…”
Section: -Degree Videomentioning
confidence: 99%
“…Second, the "novelty effect," might have played a negative role. It refers to students' overexcitement when a new "gadget" is introduced in their teaching, acting as a distraction factor derailing the learning process and diminishing the learning outcomes (Fokides & Arvaniti, 2020). Students' increased enjoyment in the holograms group might be an indicator of the presence of the "novelty effect."…”
Section: Discussionmentioning
confidence: 99%
“…For examining the learning outcomes, we deemed that a Mixed Model Analysis of Covariance (ANCOVA) was the appropriate statistical method for determining whether significant differences exist in the learning outcomes, between boys and girls, after controlling for students' prior knowledge (as recorded in the Pre-test). The following tests examined whether the data were fit for this type of statistical analysis: (i) we assessed the assumption of normality using Q-Q scatterplots (DeCarlo, 1997); (ii) we plotted the residuals against the predicted values for evaluating homoscedasticity (Field, 2013); (iii) we assessed the assumption of sphericity using Mauchly's test (Mauchly, 1940); (iv) we calculated Mahalanobis distances and compared them to a χ 2 distribution for identifying influential points in the residuals, (Newton & Rudestam, 2012); (v) we rerun the mixed model ANCOVA by including interaction terms between each independent variable and the covariate, for assessing the assumption for homogeneity of regression slopes (Field 2013); and (vi) we conducted an ANOVA for each covariateindependent variable pair, to assess covariate-independent variable independence (Field 2013). Out of the above, only the sphericity assumption was violated [χ 2 (2) = 26.90, p < .001].…”
Section: Methodsmentioning
confidence: 99%